Advancing Insights into Large-Artery Stiffening in Humans Through the Application of Multi-omics - Marie-Joe Dib (Artery Research)
Abstract A healthy aorta limits excess arterial pulsatility and protects the microvasculature from the effects of fluctuating blood flow and pressure. Aging and various pathologic states impair this cushioning function, a phenomenon known as large-artery stiffening (LAS). LAS is a common risk factor for a plethora of chronic diseases, and an important contributor to the conundrum of vascular morbidity. Importantly, LAS is pathologically different from atherosclerosis as it rather occurs primarily from changes in the medial aortic layer, and can manifest itself in the absence of plaque formation. Clinically, LAS is one of the few biological parameters that more than doubles with aging. With the advent of novel highly effective therapies for atherosclerosis, and the likely decline of other causes of death in the next few decades, prevention and treatment of increased LAS may be one of the most relevant strategies for preventing multimorbidity in aging populations in upcoming decades. LAS characterizes a high-priority therapeutic target to improve cardiovascular disease burden and associated comorbidities. This review aims to (i) provide an overview of insights from genetic research on LAS pathophysiology, and explore the scope of next-generation sequencing methods in the field arterial research; (ii) shed light on the utility of emerging state-of-the-art multi-omics approaches to unravel mechanisms underlying LAS to identify candidate therapeutic targets; (iii) highlight the potential of emerging state-of-the-art integrative multi-omics, motivating their use to address current gaps in understanding sex- and ancestry-specific mechanisms of LAS.